INTERMEDIALITY IN THE 21ST CENTURY - Cubillo Paniagua, Ruth (2013)
Frenetic and paradoxical movement marking 21st century social coexistence is producing changes in representations of reality due to changes in our representations of the world and on how we live on it. Intermediality is a useful concept because it allows us to perceive dialoguing spaces among signifying practices—or artistic and cultural processes—and media and digital devices. Some questions rise by putting this point on intermediality: What is going on when several ontological artistic traditions establish a dialogue with digital technologies’ ways of expression?  What are the consequences of this intermediality concept?  Thinking of an academic framework: Are new areas of studies created by this notion? What are the consequences of this intermediality concept on the teaching-learning processes and on the research we do in our disciplines? What are the consequences of this intermediality concept on the cultural industry and on cultural heritage of our countries?  This essay answers some of those questions while the other are rose in order to promote a necessary debate.